Complete Response With Immunotherapy: A Case of Metastatic Bladder Cancer - Balraj Singh MD; Parminder Kaur MD; Sachin Gupta MD; Nirmal Guragai MD; Michael Maroules MD (SAGE Publishing, 2021)
Bladder cancer is the most common urinary tract malignancy. Platinum-based chemotherapy is the first line of treatment in locally advanced or metastatic bladder cancer. Immunotherapy has become a novel therapy option in a broad variety of malignancies including bladder cancer. Immunotherapy is approved as first line of treatment in patients who are ineligible for platinum-based chemotherapy and second-line treatment for metastatic urothelial cancer who progressed after platinum-based treatments. We present the case of an 83-year-old female with metastatic bladder cancer who was chemotherapy ineligible and had complete response with immune checkpoint inhibitor pembrolizumab.